Detection of antibodies against Icoaraci, Ilhéus, and Saint Louis Encephalitis arboviruses during yellow fever monitoring surveillance in non‐human primates (Alouatta caraya) in southern Brazil. Issue 4 (29th April 2019) - Almeida, Marco Antonio Barreto de; Santos, Edmilson dos; Cardoso, Jáder da Cruz; Noll, Carlos Alberto; Lima, Marcelo de Moura; Silva, Franko de Arruda e; Ferreira, Milene Silveira; Martins, Lívia Carício; Vasconcelos, Pedro Fernando da Costa; Bicca‐Marques, Júlio César
Abstract: Background: Free‐ranging non‐human primates (NHPs) can host a variety of pathogenic microorganisms, such as arboviruses, which include the yellow fever virus (YFV). This study aimed to detect the circulation of YF and other arboviruses in three wild Alouatta caraya populations in forests in southern Brazil. Methods: We collected 40 blood and serum samples from 26 monkeys captured/recaptured up to four times from 2014 to 2016, searching for evidence of arboviruses by virus isolation, PCR, and neutralization tests. Results: Viral isolation and genome detection were negative; however, we detected neutralizing antibodies against the Saint Louis, Ilhéus, and Icoaraci viruses in three NHPs. Conclusions: Saint Louis Encephalitis, Ilhéus, and Icoaraci viruses circulated recently in the region. Future studies should investigate the role of NHPs, other vertebrate hosts and wild vectors in the region's arbovirus circulation and the potential risks of the arboviruses to wildlife, domestic animals, and humans.